Universal Mathematical Model and Tooth Flank Comparison of Spiral Bevel Gear and Cycloid Bevel Gear - Nie Shaowu; Deng Xiaozhong; Wei Bingyang; Li Jubo (Jixie chuandong)
Aiming to the spiral bevel gears and cycloid bevel gears,the universal mathematical model is established,and the tooth flank geometry comparison is carried out. Firstly,the two kinds of cutter head structure are analyzed,and the universal cutter head model is set up. Secondly,the cut motion and manufacture process for two systems are analyzed,and the universal mathematical model is established. On basis of solving the tooth flank,the tooth flank comparison for spiral bevel gears and cycloid bevel gears is carried out from aspect of tooth line spiral angle and tooth flank topology. This will provide theoretical guide for cycloid bevel gears rough cut by use of spiral bevel gear cutter.